Non-haloaluminate ionic liquids for low-temperature electrodeposition of rare-earth metals A review - 张启波 华一新 徐存英 李艳 李坚 董鹏 (Journal of rare earths, 2015)
The inherent advantages of ionic liquids （ILs） in electrochemistry have received extensive attention in recent two decades. As a new generation of ILs, non-haloaluminate ILs exhibit better benefits and fewer drawbacks compared to haloaluminate based ILs, which are more qualified for metal electrodeposition, especially reactive metals. In this brief review, the recent developments regard- ing the application of non-haloaluminate ILs as solvents for low-temperature electrodeposition of rare-earth （RE） metals are outlined. In addition, the current problems and an outlook on future research are presented.